Endoscopic laryngo-pharyngeal surgery for elderly patients. Issue 2 (April 2019) - Kishimoto, Yo; Harada, Hiroyuki; Funakoshi, Makiko; Miyamoto, Shin-ichi; Suehiro, Atsushi; Kitamura, Morimasa; Muto, Manabu; Tateya, Ichiro; Omori, Koichi
Abstract: Objective: Due to the rising number of elderly patients and advances in endoscopic devices, early laryngeal and pharyngeal cancers are increasingly found in elderly patients. In these cases, minimally invasive endoscopic larygo-pharyngeal surgery (ELPS) may be indicated. However, the safety and efficacy of ELPS in elderly populations has not been established. The purpose of this study was to investigate the safety, outcomes and feasibility of ELPS in very elderly patients. Methods: Between February 2010 and April 2016, 29 pharyngeal cancerous or pre-cancerous lesions in 19 patients aged 75 years or older were treated with ELPS. Twenty-six resections were performed in total, and the patients' clinical courses were reviewed. Results: Sixteen patients had multiple comorbidities and moderate to severe comorbidities were observed in 17 patients. The average surgical time and hospitalization period was 54.3 min and 18.8 days, respectively. On average, oral intake began 4.4 days after the procedure, and all patients eventually received nourishment by mouth; no percutaneous endoscopic gastrostomy dependency was observed. Complications included post-operative bleeding and aspiration pneumonia in two cases each, and all complications were safely managed. The 3-year overall survival rate was 90.2% and the 3-year disease-specific survival rate was 100%. Conclusion: ELPS was safely performed in elderly patients, suggesting that it is a feasible treatment option for pharyngeal lesions in very elderly patients.